RHYTHM OF STUDY AND UNIVERSITY TRAJECTORY - De la Barrera, María Laura; Silvio Donolo, Danilo; Rianudo, María Cristina (Anales de Psicología / Annals of Psychology, 2008)
The purpose of the work was to enunciate relationships be-tween the handling of the time and the academic achievement of univer-sity students. It was worked with 462 students that study from 1º to 5º year of different university careers. For the analyses it was subdivided to the Total Group in Group I and Group II in function of not to count or to have postponements in the final exams. They were also carried out analysis for career and for gender. The results showed the following: a) light tendency to a better management of the time of the males without reprove that of the women and the inverse relationship when it is consid-ered the group of students with reprove; b) the women have a bigger percentage of approve matters in connection with the study plan that the males; c) the group of students that doesn't have postponements presents a percentage smaller than number of approve matters with relationship to the study plan that the group of students that has postponements in its exams and; d) we confirms that the instrument is capable to measure the relationships between management of time and academic achievement.